Identification and Characterization of Escherichia coli, Salmonella Spp., Clostridium perfringens, and C. difficile Isolates from Reptiles in Brazil - Ramos, Carolina Pantuzza (Biomed Res Int, 2019)
Considering the increasing popularity of reptiles as pets and their possible role as reservoirs of pathogenic microorganisms, the aim of this study was to isolate Escherichia coli, Salmonella spp., Clostridium perfringens, and C. difficile strains from reptiles in Brazil and to characterize the isolated strains. The characterization was based on phylogenetic typing of E. coli, identification of virulence genes of E. coli, C. perfringens, and C. difficile, serotyping of Salmonella spp., ribotyping and MLST of C. difficile and antimicrobial susceptibility test of pathogenic strains. Cloacal swabs were collected from 76 reptiles, of which 15 were lizards, 16 chelonians, and 45 snakes, either living in captivity, in the wild, or as companion animals. E. coli was isolated from 52 (68.4%) reptiles, of which 46 (88.4%) were characterized as phylogroup B1. The virulence factor CNF1 of E. coli was found in seven (9.2%) sampled animals, whereas the gene of EAST1 was found in isolates from two (2.6%) reptiles. Three isolates positive for CNF1 were resistant to cephalothin, one of which was also resistant to ciprofloxacin, trimethoprim/sulfamethoxazole, and chloramphenicol, being then classified as multidrug resistant strain (MDR). Salmonella enterica was identified in 26 (34.2%) reptiles, of which 13 belonged to the subspecies enterica. Serotypes such as S. Mbandaka, S. Panama, S. Infantis, S. Heidelberg, and S. Anatum were identified. One isolate of S. enterica subsp. houtenae was resistant to cephalothin and ciprofloxacin. C. perfringens type A was isolated from six (7.8%) animals. C. difficile was isolated from three (3.9%) reptiles. Two of these isolates were toxigenic and classified into ribotypes/MLST 081/ST9 and 106/ST42, which have been previously reported to infect humans. In conclusion, reptiles in Brazil can harbor toxigenic C. difficile and potentially pathogenic E. coli and Salmonella enterica subsp. enterica, thus representing a risk to human and animal health.